Sustainable Energy Planning and Management Vol 39 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2023)
This 38th volume of the International Journal of Sustainable Energy Planning and Management presents some of the newest work within the planning of future sustainable energy systems based on renewable energy sources. In this issue, we focus on developments in Indonesia within renewable energy exploitation, electricity use in Africa and finally subsidy schemes for renewable energy exploitation in Indonesia